Ethnic identity, hegemony or resistance? Italian antifascism and the Giuseppe Garibaldi Memorial (Bahía Blanca, Argentina, 1927-1928) - Cimatti, Bruno (Documents d’Anàlisi Geogràfica, 2020)
This article addresses the relationships between space, politics and ethnic identity based on the meanings given to the Giuseppe Garibaldi Memorial in Bahía Blanca (Buenos Aires Province, Argentina) by the local antifascism movement. Particularly, we focus on the process that led to the memorial’s construction. To this end, we studied the local press, as well as documents housed in the archive of the Sociedad de Socorros Mutuos de Bahía Blanca. We observe that the monument represented at the same time an identity claim, a demonstration of hegemony and a manifestation of resistance. Our general aim is to contribute to the field of monument analysis as symbolic spatial forms of politics through the study of a case that brings into play notions of identity and power in relation to localization, dimensions and practices developed around the Garibaldi Memorial.